2019
DOI: 10.17265/2328-2142/2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Methods Used for a Capacity Estimation on Two Lane Undivided National Highways

Abstract: In these days the traffic is expanding quickly and the activity conditions on Indian roads are exceedingly heterogeneous in nature because of variety of vehicles with various static and dynamic qualities. Due to unrestricted movements all fast and slow moving vehicles without any separation, the roads will face severe congestion and lower speeds. The greater part of national and state highways in India are two lane undivided roadway. These two lane highways achieve its greatest limit soon and require consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…An examination of the previous studies on the capacity of two-lane roads reveals that these studies have primarily concentrated on three key aspects: LOS and capacity, platoon changes, and time headway and spacing headway. In the frst group of the aforementioned studies, several research works have investigated the infuence of various parameters, such as the number of platoons formed by vehicles [11], the HV [12][13][14] [15], the NFPC [16,17], speed of followers and critical H t as functional characteristics [18,19], the PTSF and the ATS [20][21][22], geometric parameters (longitudinal slope and superelevation of the road) [23,24], geometric features of the road and trafc conditions (density, speed, and the trafc fow rate) [25][26][27], and density [28] and travel speed using passenger car equivalent [29] on the LOS and road capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An examination of the previous studies on the capacity of two-lane roads reveals that these studies have primarily concentrated on three key aspects: LOS and capacity, platoon changes, and time headway and spacing headway. In the frst group of the aforementioned studies, several research works have investigated the infuence of various parameters, such as the number of platoons formed by vehicles [11], the HV [12][13][14] [15], the NFPC [16,17], speed of followers and critical H t as functional characteristics [18,19], the PTSF and the ATS [20][21][22], geometric parameters (longitudinal slope and superelevation of the road) [23,24], geometric features of the road and trafc conditions (density, speed, and the trafc fow rate) [25][26][27], and density [28] and travel speed using passenger car equivalent [29] on the LOS and road capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have developed different techniques to find PCU value for different class of vehicles. However Chandra's method is the only method that can be applied to Indian mixed traffic flow characterized by less lane discipline hence, adopted in the present study [19].…”
Section: Determination Of Passenger Car Unitmentioning
confidence: 99%
“…11. Similarly, the mean stream speed at which the maximum flow/capacity value occurs on a particular section of the highway with change in carriageway width was drawn for other sections also, and the values are tabulated in Table 2 [19]. It is observed that capacity values ranged between 1361 and 1698 PCU/hr.…”
Section: Carriageway Widthmentioning
confidence: 99%